Ecological function of key volatiles in Vitex negundo infested by Aphis gossypii - Xu, Qingxuan; Wu, Changbing; Xiao, Da; Jin, Zhenyu; Zhang, Changrong; Hatt, Séverin; Guo, Xiaojun; Wang, Su (Frontiers in Plant Science, 2023)
Herbivore induced plant volatiles (HIPVs) are key components of plant-herbivorous-natural enemies communications. Indeed, plants respond to herbivores feeding by releasing HIPVs to attract natural enemies. The present study analyses the effect of HIPVs of Vitex negundo (Lamiaceae), an indigenous plant species in northern China, on the predatory ladybug species Harmonia axyridis. Y-tube olfactometer bioassay showed that H. axyridis adults were significantly attracted by V. negundo infested by the aphid Aphis gossypii. We analyzed and compared volatile profiles between healthy and A. gossypii infested V. negundo, screened out the candidate active HIPVs mediated by A. gossypii which could attract the H. axyridis, and tested the olfactory behavior of the candidate active compounds on H. axyridis. The gas chromatography-mass spectrometry analysis showed that five volatile compounds were significantly up-regulated after V. negundo infestation by A. gossypii, and five substances were significantly down-regulated in the terpenoid biosynthesis pathway. The olfactory behavior response showed that H. axyridis has significant preference for sclareol, eucalyptol, nonanal and α-terpineol, indicating that this chemical compounds are the important volatiles released by V. negundo to attract H. axyridis. This study preliminarily clarified that V. negundo release HIPVs to attract natural enemies when infected by herbivorous insects. The description of the volatile emission profile enriches the theoretical system of insect-induced volatile-mediated plant defense function of woody plants. Applications in crop protection would lie in designing original strategies to naturally control aphids in orchards. Keywords: HIPVs, indigenous Indigenous plants, Harmonia axyridis, Chemical ecology, Woody plants